2021
DOI: 10.3390/ani11030809
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance and Meat Characteristics of Kids Fed a Red Orange and Lemon Extract

Abstract: This study evaluates the animal performance and meat characteristics of 60 Saanen suckling kids daily fed a red orange and lemon extract (RLE), rich in anthocyanins. In our methodology, after colostrum administration, animals are randomly assigned to two treatments: Treatment group (Group RLE; n = 30) that received RLE (90 mg/kg live body weight) as oral food additive, and a control group (Group CON; n = 30) that received a standard diet. Animals are slaughtered after 40 days. The RLE administration did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…The trial was carried out on 60 male and female Saanen kids. All kids were managed following the procedure described by Salzano et al [ 3 ]. After colostrum intake, all kids of the same age (4 days ± 12 h) and weight (3.1 ± 0.2 g) were divided into two groups: RLE (anthocyanins; n = 30), who received an RLE extract (90 mg/kg of live weight) (see below the composition) as an oral food additive; and CON (control; n = 30), who received saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial was carried out on 60 male and female Saanen kids. All kids were managed following the procedure described by Salzano et al [ 3 ]. After colostrum intake, all kids of the same age (4 days ± 12 h) and weight (3.1 ± 0.2 g) were divided into two groups: RLE (anthocyanins; n = 30), who received an RLE extract (90 mg/kg of live weight) (see below the composition) as an oral food additive; and CON (control; n = 30), who received saline.…”
Section: Methodsmentioning
confidence: 99%
“…Although meat consumption is mainly linked to ethical, social, and religious factors, the attraction towards this food is influenced by the rheological and sensory properties of meat, as well as by marketing strategies [ 2 ]. A great challenge that the meat industry is facing is the increased production costs linked to the negative environmental impacts perceived by consumers [ 3 ]. To overcome these problems, many agroindustrial by-products have been proposed as alternative feed sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One unit of enzyme activity is defined as the amount of enzyme that is required to degrade 1 micromole of H 2 O 2 in 1 min. The GPx activity was measured following the GSH oxidation rate by tert -butyl hydroperoxide, catalyzed by GPx [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, RLE has been previously tested as an oral additive for goat kids, showing ameliorated juiciness and reduced color deterioration of the kids’ meat as a result of delayed lipid oxidation. This resulted in an improved fatty acid profile and thus healthier meat for human consumption [ 18 ]. It has also been previously demonstrated that goat kids fed on a diet supplemented with RLE showed significantly increased neuropeptide Y-(a neuropeptide involved in food intake regulation) immunoreactive cells in the abomasal epithelium and pancreatic islets, representing a baseline for future studies on the interaction between neuropeptides and polyphenols [ 19 ].…”
Section: Discussionmentioning
confidence: 99%